Is my boson sampler working?. (7th April 2016) - Bentivegna, Marco; Spagnolo, Nicolò; Sciarrino, Fabio
Abstract: Is it possible to assess the correct functioning of a quantum device which eludes efficient computation of the expected results? The BosonSampling protocol is one of the best candidates to experimentally demonstrate the superior computational power of quantum mechanics, but the problem of its results certification requires the development of new methodologies, when the size of the problem becomes too large for a complete classical simulation. A recent work (Walschaers et al 2016 New J. Phys. 18 032001) has provided a significant step forward in this direction, by developing a statistical test to identify particle types in a many-body interference pattern. This tool can be applied in a general scenario to assess and investigate multi-particle coherent dynamics.